Diagnostic Impact of Crypt Branching in Patients With Crohn's Disease: A Validation Study - Lang-Schwarz, Corinna; Rubio, Carlos A.; Vieth, Michael (Anticancer Research, 2022)
BACKGROUND/AIM: Crypt branching in inflammatory bowel diseases (IBD) was previously classified into symmetric (CSB) and asymmetric branching (CAB). We aimed to validate the inter-rater agreement of the assessment of crypt branching (also called crypt fission) in patients with Crohn's disease (CD) and to elucidate its potential diagnostic impact. PATIENTS AND METHODS: A total of 100 colon biopsies from patients with active CD were analyzed. Two cohorts of patients with ulcerative colitis (UC) and infectious colitis, respectively, served as controls (UC-controls/infectious controls). Three pathologists scored the total number of branching crypts (TBC) as well as the number of CSB and CAB. RESULTS: Inter-rater agreement ranged from moderate to good for TBC and CAB in the study cohort. The study cohort showed significantly higher counts of TBC, CSB, and CAB than the infectious controls (p<0.001 for TBC, p=0.008 for CSB, and p<0.001 for CAB). Cases with CD showed more TBC and CAB compared to cases with UC (p=0.001 each). CONCLUSION: Inter-rater agreement for crypt branching is reliable in patients with CD. Crypt branching was shown to be an additional histologic feature to distinguish active CD from infectious colitis. Additionally, it could be helpful in the distinction between CD and UC.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Crohn’s disease; Crypt branching; histopathology